(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
A power system suffers from losses that can cause tragic consequences. Reactive power presence in the power system increases system losses delivered power quality and distorted the voltage. As a result, many studies are concerned with reactive power compensation. The necessity of balancing resistive power generation and absorption throughout a power system gave birth to many devices used for reactive power compensation. Static Var Compensators are hunt devices used for the generation or absorption of reactive power as desired. SVCs provide fast and smooth compensation and power factor correction. In this paper, a Fuzzified Static Var Compensator consists of Thyristor Controlled Reactor (TCR) branch and Thyristor Switched Capacitors branches for reactive power compensation and power factor correction at the load side is presented. The system is simulated using Simulink using a group of blocks and equations for measuring power factor, determining the weightage by which the power factor is improved, determining the firing angle of TCR branch, and capacitor configuration of TSC branches. Furthermore, a hardware prototype is designed and implemented with its associated software; it includes a smart meter build-up for power monitoring, which displays voltage, current, real power, reactive power and power factor and SVC branches with TRIAC as the power switching device. Lastly, static and dynamic loads are used to test the system’s capability in providing fast response and compensation. The simulation results illustrated the proposed system’s capability and responsiveness in compensating the reactive power and correcting the power factor. It also highlighted the proportional relation between reactive power presence and the increased cost in electricity bills. The proposed smart meter and SVC prototypes proved their capabilities in giving accurate measurement and monitoring and sending the data to the graphical user interface through ZigBee communication and power factor correction. Reactive power presence is an undesired event that affects the equipment and connected consumers of a power system. Therefore, fast and smooth compensation for reactive power became a matter of concern to utility companies, power consumers and manufacturers. Therefore, the use of compensating devices is of much importance as they can increase power capacity, regulate the voltage and improve the power system performance.